Penggunaan Kolase Karir Sebagai Intervensi Terapi Untuk Pengambilan Keputusan Karir Siswa SMK - Wahyuningsih, Diana Dewi; Nugraha, Imam Setya (IAIN Kudus, 2021)
Use of Career Collage as a Therapeutic Intervention for Career Decision Making for Vocational High School Students. This study aims to investigate the use of career collage as a therapeutic intervention for career decision making in vocational high school students. This research belongs to the type of library research, namely, by recording all findings and combining all findings, either theory or new findings about career collage, analyzing all findings from various readings and providing critical ideas about career collage as a therapeutic intervention for decision making. student career. The results showed that career collage is a series of activities designed by counselors through the creation of a vision board as part of students' self-expression strategies to build self-identity. Using a cognitive social career theory framework, to promote identity exploration, increase self-efficacy beliefs and the development of career aspirations.Keywords: Career Collage; Therapeutic Interventions; Career Decision Making